EFEKTIVITAS PENERAPAN SISTEM INFORMASI MANAJEMEN NIKAH (SIMKAH) DALAM PELAYANAN KARTU NIKAH DIGITAL DI KANTOR URUSAN AGAMA KECAMATAN TANGGETADA - Elvina Yusriani; Nursamsir; Fetni (Halu Oleo University, 2025)
This research aims to examine the effectiveness of the implementation of the Marriage Management Information System (SIMKAH) in delivering digital marriage card services at the Office of Religious Affairs (KUA) in Tanggetada District. The study employs a descriptive qualitative approach. The research was conducted at the KUA office and involved key informants such as the Head of KUA, SIMKAH operator, administrative staff, other KUA personnel, and members of the local community. Both primary and secondary data sources were used in this research. The findings indicate that the use of SIMKAH for digital marriage card services in Tanggetada District has not yet reached optimal effectiveness. Several issues were identified, including delays in issuing the digital marriage cards, limited access to the system among the public, and a lack of public understanding of how SIMKAH works. These challenges are particularly evident among individuals who are unfamiliar with digital technology or have not received sufficient information about the system.